2021
DOI: 10.1039/d0bm02211j
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid-cell membrane-coated nanocomplex-loaded chikusetsusaponin IVa methyl ester for a combinational therapy against breast cancer assisted by Ce6

Abstract: Breast cancer is the most common cancer in women, which occurs mostly with poor outcomes. Our objective was to endow synthetic lethality to phytoconstituent chikusetsusaponin IVa methyl ester (CSME, S),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…developed a drug delivery system based on hybrid CCM‐functionalized liposomes that were loaded with the cytotoxic compound chikusetsusaponin IVa methyl ester (CSME) and photosensitizer chlorin e6 (Ce6) for combinational therapy. [ 49 ] In their approach, the hybrid CCMs derived from RBCs and 4T1 cells were fused into the CSME‐loaded liposomes under sonication to confer the liposomes with specific targeting ability and extended blood circulation time. Subsequently, the Ce6 was loaded into the bilayer and cavity structure of the liposomes, followed by further modification of Arg‐Gly‐Asp (RGD) onto the liposome surface to strengthen their targeting ability.…”
Section: Engineered Cancer Cell Membranes For Cancer Theranosticsmentioning
confidence: 99%
“…developed a drug delivery system based on hybrid CCM‐functionalized liposomes that were loaded with the cytotoxic compound chikusetsusaponin IVa methyl ester (CSME) and photosensitizer chlorin e6 (Ce6) for combinational therapy. [ 49 ] In their approach, the hybrid CCMs derived from RBCs and 4T1 cells were fused into the CSME‐loaded liposomes under sonication to confer the liposomes with specific targeting ability and extended blood circulation time. Subsequently, the Ce6 was loaded into the bilayer and cavity structure of the liposomes, followed by further modification of Arg‐Gly‐Asp (RGD) onto the liposome surface to strengthen their targeting ability.…”
Section: Engineered Cancer Cell Membranes For Cancer Theranosticsmentioning
confidence: 99%
“…A recent study showed that, compared with their free forms, RBC membrane modification can mediate a greater enhancement of the cell internalization of drugs . RBC membranes are the most popular natural carriers and can efficiently combine with other membranes and regulate the circulation time of HM@BNPs …”
Section: Biomedical Applications Of Hm@bnpsmentioning
confidence: 99%
“…However, the main limitations faced by conventional phototherapeutic agents include bioadhesion and opsonization by serum proteins in the bloodstream, rapid recognition and clearance by immune sentinels and mononuclear phagocyte system (MPS), and low accumulation in action sites . Cell-membrane camouflaging has great potential to overcome these issues due to their abundant surface proteins and biological features, including a lack of immunogenicity, superior blood circulation, or homologous targeting, along with the preservation of the photophysical properties of phototherapeutic nanoparticles . For instance, the long circulation time of RBC membranes is of great significance for improving the performance of photobased applications. , The adhesion properties of platelets can improve the inhomogeneous distribution of phototherapeutic agents in phototherapy, as the postinjury feedback caused by thermal damage leads to additional recruitment of platelets and then promotes the targeting ability of delivery system .…”
Section: Biomedical Applications Of Hm@bnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is exciting is that with the continuous advancement of bionic technology, a hybrid cell membrane (HMC) is formed by fusing cell membranes from different sources, which can integrate different membrane functions into a bionic platform. For instance, Xie et al [55] fuses the RBCm and the CCM into a mixed cell membrane to assemble a liposome-based nanoparticle (LSCMR NPs) containing the photosensitizer Ce6 and the chemotherapeutic drug chikusetsusaponin IVa methyl ester. According to SEM and DLS analysis, the zeta potential and average diameter of LSCMR NPs increased slightly.…”
Section: Bionic Nanoplatformsmentioning
confidence: 99%